Assessment of External Economic Cooperation in the Aspect of Transport Development of the Greater Tumen Initiative - Vakulenko Sergei; Nekhoroshkov Evgeniy; Majercak Peter; Karyshev Mikhail (SHS Web of Conferences, 2021)
Research background: The aim of the scientific contribution is to analyze the aspect of Transport Development of the Greater Tumen Initiative. Economic cooperation among the countries of the Greater Tumen Initiative (GTI) is the basis for interaction in various fields, especially transport. Purpose of the article: However, taking into account the prevailing trends in Europe-Asia transportation, it is not entirely correct to make the implementation of GTI transport projects dependent on prospective transit freight flows. At first, it is necessary to concentrate on the transport support of foreign trade flows directly between the GTI member countries. Methods: We propose to assess the stability of foreign trade flows as a cargo base (current and potential) of transport projects within the GTI by absolute time series, which reflects the trend (or its absence, i.e. each next level is higher or lower than the previous one) and its stability, as well as by relative time series, i.e. growth rates, which reflects the stability of the change rate (the growth rate of each subsequent period is higher or lower than the previous one). Findings & Value added: Based on the results of the assessment of foreign trade flows between the member countries, that forms the current and potential cargo base of transport projects, it was concluded not only about a high degree of stability and potential of foreign economic cooperation, but also about the need of extra measures for its further intensifying, including foreign trade transport services improvement.